Optimization of tenocyte lineage-related factors from tonsil-derived mesenchymal stem cells using response surface methodology - Kwon, Soon Sun; Kim, Hyang; Shin, Sang Jin; Lee, Seung Yeol (Journal of Orthopaedic Surgery and Research, 2020)
Background: In order to optimize the tenogenic differentiation of mesenchymal stem cells (MSCs), researchers should consider various factors. However, this requires testing numerous experimental settings, which is costly and time-consuming. We aimed to assess the differential effects of transforming growth factor beta-3 (TGF-β3) on the tenogenesis of tonsil-derived MSCs (T-MSCs) and bone marrow-derived MSCs (BM-MSCs) using response surface methodology (RSM). Methods: Bone marrow and tonsillar tissue were collected from four patients; mononuclear cells were separated and treated with 5 or 10 ng/mL of TGF-β3. A full factorial experimental design with a categorical factor of 0 was employed to study the effect of tension based on T-MSCs. Eighty-four trials were fitted with RSM and then used to obtain mathematical prediction models. Results: Exposure of T-MSCs and BM-MSCs to TGF-β3 increased the expression of scleraxis (SCX), tenomodulin (TNMD), decorin, collagen I, and tenascin C. Expression of most of these factors reached a maximum after 2-3 days of treatment. The model predicted that the values of the tenocyte lineage-related factors assessed would be significantly increased at 2.5 days of culture with 2.7 ng/mL of TGF-β3 for T-MSCs and at 2.3 days of culture regardless of TGF-β3 concentration for BM-MSCs. Conclusions: This study demonstrated that the RSM prediction of the culture time necessary for the tenogenic differentiation of T-MSCs and BM-MSCs under TGF-β3 stimulation was similar to the experimentally determined time of peak expression of tenocyte-related mRNAs, suggesting the potential of using the RSM approach for optimization of the culture protocol for tenogenesis of MSCs.
Keywords: Aged; Aged, 80 and over; Cell Culture Techniques; Cell Differentiation; Cell Lineage; Cells, Cultured; Female; Humans; Male; Mesenchymal Stem Cells; Palatine Tonsil; Tenocytes; Bone marrow-derived mesenchymal stem cells; Design of experiments; Response surface methodology; Tenocyte; Tonsil-derived mesenchymal stem cells